COMPREHENSIVE REVIEW OF IMAGING MODALITIES FOR EVALUATING ABDOMINAL AORTIC ANEURYSMS - Odai Abdullah Altoori, Ali Hussaien Alsawas, Abdulmajeed Jowebir Alrefaei, Rakan Mohammed Alrehaili, Abdulelah Abdulrazeq Almalawi, Fayez Hulayyil Alharbi, Maram Sulaiman Almuzaini (Chelonian Research Foundation, 2023)
AAA is determined to be a type of vessel disease that involves deadly outcomes with a remarkably high mortality rate. With the evaluation of AAAs conducted on time and properly, clinicians can use the right decision-making decision-making in the clinical process and reach the best outcomes for patients. In this article, a review of imaging modalities will be given, in particular, the ones that are used to evaluate abdominal aortic aneurysms (AAA) – they are Ultrasound, Computed Tomography Angiography (CTA), Magnetic Resonance Angiography (MRA), and plain radiography. The factors that can make a critical difference are incorporated in these examples. These include diagnostic performance, access, and risk. Economic factors are also discussed. Another step of the review is looking into the new methods and developing imaging techniques, which will be the answer to the problem of AAA discovery and assessment. This review seeks to furnish data on the image qualities and drawbacks of specific imaging modalities in an attempt to guide clinicians in choosing the most suitable imaging approach for the surveillance of AAAs. Keywords: abdominal aortic aneurysm, imaging modalities, ultrasound, computed tomography angiography, magnetic resonance angiography, plain radiography.